Heat stress affects the functionality of the ovine cumulus-oocyte complex and subsequent in vitro embryo production - Alicia Martín-Maestro; Irene Sánchez-Ajofrin; María Iniesta-Cuerda; Daniela Medina-Chávez; Carolina Maside; María Rocío Fernández-Santos; Julián Garde; Ana Josefa Soler (Scientific Reports)
Abstract Global population growth requires an increase in the production of food, particularly meat, with an expected increase in sheep farming. However, climate change challenges livestock management, with heat stress negatively impacting reproductive performance. In vitro embryo production (IVP) in sheep farming is promising, although optimizing embryo quality and efficiency remains challenging. Heat stress impairs oocyte developmental competence, affecting IVP outcomes. This study investigated the effects of season on oocyte quality and embryo production given seasonal variations in the temperature and temperature–humidity index (THI) and in vitro-induced heat stress. In the first experiment, ovaries were collected in four seasons (winter, spring, summer and autumn), with differences in THI, and in the second experiment, ovaries were exposed to 30 °C (control), 38.5 °C, 40 °C and 41 °C. The results indicated that elevated summer temperatures significantly compromised oocyte and cumulus cell viability, DNA integrity, mitochondrial distribution, and blastocyst quality. These detrimental effects persisted into autumn, likely due to a carry-over effect from summer heat stress. Furthermore, in vitro exposure to temperatures at or above 38.5 °C led to marked decreases in oocyte quality and blastocyst rates. Understanding these effects is essential for developing strategies to mitigate heat stress and enhance reproductive outcomes in sheep.